KAJIAN HADIS ERA ANDROID (Telaah Aplikasi ‘Masuk Surga’ Karya Ahmad Lutfi Fathullah) - Fahrudin Fahrudin (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
Hadith studies have experienced very rapid development. This is because many developing various applications or software that can facilitate the study of Hadith. The application and software are then not only a tool in the research activities of Hadith, but also for the benefit of studying the Hadith by the general public. Thus, the application or software must be developed so that it can be sought after and used by the general public. One such application is "Entering Paradise" developed by the Hadith Study Center. This application is based on Android so that it can be used easily in all places and times. This application contains the Hadiths from the book of Riyadh al-Saliheen and is presented in different themes. The pattern of presentation is very interesting because it represents human life from the beginning of knowing Islam to death and life after death. With descriptive-analytical methods, this paper will examine the application 'Go to Heaven', starting from the background of its development, features, patterns of presentation of the Hadith and their advantages and disadvantages.